2021
DOI: 10.3389/fcell.2021.660233
|View full text |Cite
|
Sign up to set email alerts
|

Selective Anti-melanoma Effect of Phosphothioated Aptamer Encapsulated by Neutral Cytidinyl/Cationic Lipids

Abstract: BC15-31 is a DNA aptamer that targets heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1), which plays a crucial role in the process of pre-RNA maturation and is also essential for the rapid proliferation of tumor cells. In this research, we modified BC15-31 with a phosphorothioate (PS) backbone, LNA, and 2-O-MOE to enhance its stability and target affinity. In addition, a neutral cytidinyl lipid (DNCA) and a cationic lipid (CLD) were mixed to encapsulate modified aptamers with the aim of improving their cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…BC15-31, a heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1)-specific aptamer, was chemically modified with a phosphorothioate backbone for its antitumor application in vivo. The unmodified BC15-31 aptamer was significantly degraded after 2 h incubation with 20% fetal bovine serum, while the all-site modified aptamer remained stable for 8 h [ 93 ]. The modification of aptamers with thiophosphate analogues can not only improve the nuclease stability of aptamers but also effectively improve the affinity between aptamers and targets.…”
Section: Post-selex Optimization Of Aptamersmentioning
confidence: 99%
“…BC15-31, a heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1)-specific aptamer, was chemically modified with a phosphorothioate backbone for its antitumor application in vivo. The unmodified BC15-31 aptamer was significantly degraded after 2 h incubation with 20% fetal bovine serum, while the all-site modified aptamer remained stable for 8 h [ 93 ]. The modification of aptamers with thiophosphate analogues can not only improve the nuclease stability of aptamers but also effectively improve the affinity between aptamers and targets.…”
Section: Post-selex Optimization Of Aptamersmentioning
confidence: 99%
“… 37 Previous studies have shown that DCP (cytidinyl/cationic mixed lipids, DNCA/CLD/DSPE-PEG, Table S1 ), a novel transfection system based on hydrogen bonding and π-π stacking, can deliver various ON drugs into cells with high efficiency. 38 , 39 , 40 , 41 , 42 , 43 The combined encapsulation effect of various intermolecular forces makes the ratio of the formulation components more flexible depending on the context, and the cationic lipid levels can be negligible. Compared with sorafenib, DCP-CT102 achieved greater efficacy at a dose of ∼2 mpk administered every other day.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of hydrogen bonds, π−π stacking, and electrostatic interaction, neutral cytidinyl lipid DNCA and cystine skeleton CLD were designed and synthesized. This delivery system could transfect ON drugs such as siRNAs, 28−31 aptamers, 32,33 ASO, 34 and mRNA 35 into cells, and it has achieved intratumoral administration to effectively inhibit tumor growth in vivo. 36 Insulin-like growth factor type I receptor (IGF1R) and its ligands IGF-I and IGF-II, which are abnormally expressed in a variety of malignant tumors, are closely related to tumor growth, metastasis, and radiotherapy/chemotherapy resistance.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of hydrogen bonds, π–π stacking, and electrostatic interaction, neutral cytidinyl lipid DNCA and cystine skeleton CLD were designed and synthesized. This delivery system could transfect ON drugs such as siRNAs, aptamers, , ASO, and mRNA into cells, and it has achieved intratumoral administration to effectively inhibit tumor growth in vivo …”
Section: Introductionmentioning
confidence: 99%